Evaluation of Feed Additive Nutmeg Seed Powder (Myristica fragnans Houtt) on Egg Quality Characteristics and Egg Production - Rinny Leke; Erwin Wantasen; Florencia Sompie; Hengky Kiroh; Nontje Kumajas; Jacquline Laihad; Charles Kaunang; Ratna Siahaan (Journal of Applied Veterinary Science And Technology, 2024)
Background: Poultry production faces food safety issues. Increasing public awareness of the risk of developing pathogen cross-resistance to antibiotics has resulted in the gradual elimination of antibiotics for therapeutic purposes. Transitioning from antibiotic supplementation to adoption of effective alternative control methods. Prohibition of the use of antibiotics in the feed of laying hens increase the usage of natural antibiotics from plants. The addition of feed additive nutmeg seed powder as helps the body to fight stress with anti-oxidative properties, improves immune function and restores normal physiology. The addition of polyphenols, withanolides, vitamins, minerals and other herbal products in the feed has shown considerable improvement in health in poultry. Purpose: This study aims to study the evaluation of feed additive nutmeg (Myristica fragrans Houtt) seed powder on egg quality characteristics and egg production. Method:  A number of 200 chickens were used with 5 treatments and 5 replications and each repetition was occupied by 8 laying hens. The treatment given was R0 = 100% Basal Feed/BF (without nutmeg flour), R1 = 0.5% Nutmeg Seed Powder (NSP) + 99.5% BF, R2 = 1% NSP + 99% BF, R3= 1.5% NSP+ 98.5% BF, R4 = 2% NSP+ 98% BF. Results:  The results of the study were egg weight, Haugh Unit, egg mass, shell index, egg shell thickness, yolk index, yolk color, egg yolk protein, egg white protein, egg yellow fat, cholesterol which gave very significantly different results (p<0.01). Feed Consumption (g/bird), HDP (%), Conversion (p>0,05). Conclusion:  The feeding up to 2% of nutmeg seed powder given to laying hens can improve the egg quality characteristics and egg production.